Electronic Land Certificates: Its Goals and Challenges - Elza Syarief (Publindo Akademika, 2021)
Recently, the Government through the Ministry of ATR/BPN launched a plan to adopt digital transformation. In accordance with this goal, there is a new breakthrough in making land certificates, namely electronic land certificates. This study aims to find out the challenges and results achieved in the application of electronic land certificates. The results showed that the transformation from physical certificates to electronic certificates takes time. The land certificate was an implementation of the Regulation of the Minister of ATR/Head of BPN No. 1 of 2021 concerning Electronic Certificates. The issuance of electronic certificates could later be done through land registration for the first time for unregistered land. In addition, the change of physical certificates into electronic certificates for registered land can be done voluntarily by the owner by visiting the land office